The UK's 2012 Climate Change Risk Assessment: How the rational assessment of science develops policy-based evidence. (6th September 2016) - Tangney, Peter
Abstract: This paper describes the views of participants in the UK's 2012 Climate Change Risk Assessment, to provide insights into the development and use of scientific evidence for complex social-ecological policy problems like climate adaptation. Interviews confirm that 'linear-rationalist' prescriptions commonly used for the ex-ante policy appraisal of science facilitate processes of politicisation, providing a façade of legitimacy behind which the inevitable normative decisions required during evidence development can be safely made for political ends. The UK's risk assessment was used tactically rather than instrumentally at all levels of government to garner political legitimacy for various policy portfolios. The tactical or political use of evidence occurred overtly, as an aid during policy advocacy, and covertly through the politicisation of expert knowledge. However, the linear-rationalist assessment method was largely inadequate for characterising climate change problems, for making instrumental use of climate science and suppressed broader institutional learning about climate-related policy-making.